Investigation of seafloor craters and mounds in the central Barents Sea - Sørbø, Magnus (UiT The Arctic University of Norway, 2016)
Recently acquired datasets of multibeam, echosounder and seismic data reveal the geomorphology and distribution of seafloor craters and mounds in central Barents Sea. The study found 288 craters, 227 pingos and 119 gas flares in the area, each with its own distinctive appearance. The majority of pingos lie inside or close to craters. This indicate a connection between the two features. Inspection of the subsurface shows several faulting systems and migration pathways underneath the seabed features. Migration of hydrocarbons supplies the shallow subsurface with gas, trapping the gas inside cages of ice, to become gas hydrates. Models of the gas hydrate stability zone (GHSZ) show conditions sufficient to sustain a considerable amount of hydrates in the subsurface. Signs of gas hydrate BSRs are observable inside and outside of the study area. Four major glaciations covered the study area during Late Cenozoic. This have resulted in different climatic events, affecting the GHSZ. The GHSZ has decreased significantly since Last Glacial Maximum, leading to vast dissolution of gas hydrates and release of free gas. The pressure change, caused by the ice sheet movement, reactivated faults and enhanced supply of gas to the shallow subsurface. Gas flares at the seafloor indicate an active fluid system. The hydrates push the seafloor upwards to create submarine pingos. This has caused one or several blowouts after reaching the threshold limit of the seafloor. The depressions, created by the blowouts, are interpreted to consist of 20 % pockmarks (50-100 m), 53 % large pockmarks (100-300 m) and 27 % fluid flow craters (>300m).